Analisis Literasi Membaca Mahasiswa STAI Siliwangi Garut - Novela, Greria Tensa; Chaeruman, Uwes Anis; Rahmawati, Reni (Universitas Negeri Jakarta, 2024)
Along with the development of science and technology, books are starting to be replaced by electronic devices, new technology has brought great benefits and opportunities in terms of getting information more quickly and in a more efficient way. Unfortunately, the ease of getting information has made people's awareness of the importance of having the ability to read increasingly disappear. . This is proven by survey results from various international institutions regarding the low reading ability of Indonesian students. The efforts made by the government through the recent reading literacy policy have provided changes for the better, although not yet significant, therefore, research was conducted on 100 students using PISA questions to find out what difficulties students faced in taking the PISA test from the results of the analysis. The results found that students had difficulty in taking the PISA test, namely questions related to reflecting and evaluating text in tabular form extensively, analyzing the combination of information in non-continuous images and graphs, integrating and interpreting text appropriately, and reflecting and evaluating text in table continuous.